Religion, Ideology of Domination, and Nationalism: Kuroda Toshio on the Discourse of Shinkoku - Rambelli, Fabio (Japanese journal of religious studies, 1996)
This essay examines Kuroda Toshio's analysis of the concept of shinkoku (land of the kami) as it evolved in medieval Japan, and the part this concept played in the development of a state ideology. Kuroda showed that the shinkoku discourse developed within the exo-esoteric system (kenmitsu taisei), the dominant politico-religious ethos of the times, as a reactionary ideology employed against new tendencies and movements in medieval Japanese society that were potentially disruptive for the ruling regime. This discourse eventually came to constitute the basic conceptual paradigm for reactionary ideology and politics in Japan until the present day.